Prevalence and Intensity of Ectoparasites in Silver Barb (Barbonymus gonionotus) Cultivate by the Fasting Method in a Polyculture System - Aueresta Gita Syahbila; Syahbila, Aueresta Gita; Syakuri, Hamdan; Nugrayani, Dewi (Indo Journal of Multidisciplinary Science, 2026)
Silver barb (Barbonymus gonionotus) is one of the most widely consumed freshwater fish species in Indonesia. Ectoparasitic infections can interfere with fish culture practices, particularly under intermittent fasting regimes; therefore, continuous monitoring is required to anticipate potential infestations. This study aimed to identify ectoparasite species, evaluate the effect of fasting on ectoparasite intensity, and determine the prevalence of ectoparasites in silver barb cultured in a polyculture system. This study employed an experimental method using a Completely Randomized Design (CRD) consisting of three fasting treatments with ten replicates each. Fish sampling was conducted using random sampling techniques. The treatments included fasting on Monday (P1), fasting on Monday and Thursday (P2), and fasting on Monday, Wednesday, and Friday (P3). The ectoparasites identified were Monogenea, Trichodina sp., and Ichthyophthirius multifiliis. The results indicated that different fasting treatments did not significantly affect ectoparasite intensity. The prevalence of ectoparasites ranged from 10% to 100% across treatments. Throughout the cultivation period, water quality parameters remained within the acceptable standards for Class III water quality.